(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
This research explores an informal science program (ISP) in fulfilling the needs of talented and gifted middle school students. Specifically, it discusses the need of teachers continued professional development and the unique challenges and opportunities inherent in instructing gifted middle school students. It further focuses on characteristics of successful teaching strategies and methods for identifying and training teachers. The study uses a constructivist framework to examine teaching methods and suggests that constructivism is an appropriate method for instructing gifted middle school students. The research reflects the results of an embedded descriptive multiple case study of six teachers in the informal science program, an initiative to provide middle school students in rural midwestern states with opportunities for accelerated learning in science.